SISTEM INFORMASI AKUNTANSI PERHOTELAN BERBASIS WEB - Putu Roy Nurbhawa; Anak Agung Gede Bagus Ariana; I Nyoman Bagus Suweta Nugraha (Jurnal Bangkit Indonesia, 2021)
Bakung Ubud Resort and Villa is an accommodation that provides room lodging services, food and beverages, and laundry. Currently, information data processing for financial reports only limited for revenue statement and it’s done manually. The accounting information system used is still desktop-based so that financial reports cannot be presented in real-time. The accounting information system is not integrated with other departments causing financial reports to be irrelevant. Bakung Ubud uses this information system to support operations in presenting financial reports and seeing company profits. To present relevant reports, it is necessary to design a web-based system that can be integrated with other departments. This system will help the finance department to carry out transactions that occur in the company to present financial reports. Accounting information system based on the web and using MySQL as a database. The development method uses the waterfall method. The results of system testing using black-box testing are thirty-seven (37) testing of twelve (12) modules it can be concluded that accounting information systems that are integrated with other departments help manage data in the finance department. The features contained in the accounting information system in Bakung Ubud can manage and produce relevant financial reports for the company.